2016
DOI: 10.9790/0853-150802143146
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine as an adjuvant for Hypotensive Anaesthesia during Functional Endoscopic Sinus Surgery (FESS)

Abstract: Introduction:FESS (Functional Endoscopic Sinus Surgery) is done via endoscope and the area is highly vascular thus it becomes important to minimize bleeding. Hence we require hypotensive anesthesia. Various drugs have been used for the purpose: nitroglycerine (NTG), sodium nitroprusside(SNP),propofol,beta blockers, calcium channel blockers, higher concentrations of inhalational anesthetics etc. Since all these drugs have certain limitations there was a search for safer and more effective drug .Dexmedetomidine,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 14 publications
0
24
0
Order By: Relevance
“…We also assessed adverse effects such as hemodynamic instability and compared them between the dexmedetomidine and control groups. The administration of a loading dose of dexmedetomidine (1 μg/kg) over 10 minutes, followed by administration of the maintenance dose (range, 0.2 to 0.7 μg/kg/hour) is recommended for patient sedation, regardless of age . The enrolled trials complied with the recommended regimens for maintaining adequate sedation during nasal surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We also assessed adverse effects such as hemodynamic instability and compared them between the dexmedetomidine and control groups. The administration of a loading dose of dexmedetomidine (1 μg/kg) over 10 minutes, followed by administration of the maintenance dose (range, 0.2 to 0.7 μg/kg/hour) is recommended for patient sedation, regardless of age . The enrolled trials complied with the recommended regimens for maintaining adequate sedation during nasal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Outcomes analyzed were intra‐ and postoperative pain; postoperative (24 hours) analgesic requirements (dose of postoperative opioids or nonopioid analgesics); occurrence of postoperative nausea and vomiting (PONV) (incidence or percentage of patients); intraoperative hypotension; intraoperative bradycardia; intraoperative desaturation; occurrence of patient satisfaction (incidence or percentage of patients); and operative blood loss . In the enrolled study for analgesics, one study used diclofenac (nonsteroidal antiinflammatory drug) as the additional analgesic, and the remaining studies used opioids such as tramadol and fentanyl as the additional analgesics. In terms of bradycardia and hypotension, these states were defined as the hemodynamic instabilities to be treated with 0.5 mg of atropine injection or 5 mg of ephedrine injection individually, and were monitored at regular intervals during the operation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Dexmedetomidine, an alpha-2 adrenoceptor agonist, has sympatholytic, sedative, anesthetic, and algesic effects-as well as vasoconstrictive effects. 6,7 During the past few years, dexmedetomidine has reportedly been used in pediatrics as a premedication, a sedation agent used in pediatric intensive care units, an adjunct to inhaled anesthetic agents, and a drug for both prophylaxis and treatment of EA after general anesthesia. 8 The results of several recent studies on the use of perioperative adjuvant dexmedetomidine are encouraging, showing beneficial effects on postoperative morbidities such as pain and agitation in pediatric patients.…”
Section: Introductionmentioning
confidence: 99%
“…7 Previous studies have shown that dexmedetomidine could be used as a sedative in the paediatric intensive care unit and as an adjunct to volatile anaesthetics. 2,16 It has also been demonstrated that dexmedetomidine decreases post-operative pain and agitation. 17 For these reasons, dexmedetomidine may be effectively used to treat post-operative pain and agitation in children undergoing adenotonsillectomy surgery using sevoflurane.…”
Section: Ta B L E 1 Comparison Of Baseline Characteristics Of Patientmentioning
confidence: 99%